Assessing the impact of digital supply chain management on the sustainability of construction projects - Shahid Aziz; Prince Kumar; Anwar Baz Khan (Review of Business and Economics Studies)
Purpose: The implementation of digital supply chain management (DSCM) has brought about a paradigm shift in the construction industry, which is known for its complex and dynamic nature. This study examines the advantages of implementing a digital supply chain into building projects, focusing on efficient procurement, real-time tracking, and its effects on the sustainability of the project. Methodology: A stratified sampling approach is used in the research methodology to collect quantitative data from construction project managers and supply chain specialists using surveys and questionnaires. The study’s main objective is to measure how improved stakeholder coordination, real-time tracking, and streamlined procurement procedures affect sustainability and efficiency. Findings: The results of this study highlight the significant advantages of DSCM in raising the effectiveness of building projects. The results include shortened lead times, improved supply chain visibility, streamlined procurement procedures, and optimal resource allocations. Originality and conclusions: This paper is focused on the potential difficulties and roadblocks to a successful DSCM implementation. The study provides insightful information for decision-makers and practitioners in the construction sector. To successfully apply DSCM, organizations need to make investments in technology and training, improve teamwork, and create risk-reduction plans.